Perbandingan Strategi Pemasaran Tradisional Dengan Pemasaran Melalui Influencer dalam Mempengaruhi Minat Beli Pada Audiens Muda - Cindy Firstiananda Deka; Alifah Niser (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In the ever-evolving digital era, marketing is undergoing significant changes. Rapid developments in the world of marketing demand a deep understanding of effective methods in reaching the target market. The purpose of this research is to compare how influencer marketing and traditional marketing strategies can influence young audiences' purchase intention. This research uses a qualitative approach with a literature study method, and focuses on the influence of influencer marketing and traditional marketing strategies on young consumers' purchase intention. Influencer marketing is an important strategy for market segmentation, building trust, and faster turnaround time. With a large social media following, digital influencers can significantly influence consumers' purchase intention. Authenticity and personal engagement are key aspects of influencer marketing. Combining traditional and influencer marketing can create a responsive strategy for young audiences. Influencer marketing and traditional marketing significantly impact consumer interest and advertising effectiveness. The marketing mix increases trust and confidence, which leads to increased purchase decisions. Understanding the influence of influencers can help companies develop effective strategies, allocate resources wisely and increase profits.